The presentation, management and outcome of inflammatory breast cancer cases in the UK: Data from a multi-centre retrospective review. (December 2018) - Copson, E.; Shaaban, A.M.; Maishman, T.; Moseley, P.M.; McKenzie, H.; Bradbury, J.; Borley, A.; Brzezinska, M.; Chan, S.Y.T.; Ching, J.; Cutress, R.I.; Danial, I.; et al.
Abstract: Objectives: Inflammatory Breast cancer (IBC) is a rare but aggressive form of breast cancer. Its incidence and behaviour in the UK is poorly characterised. We collected retrospective data from hospitals in the UK and Ireland to describe the presentation, pathology, treatment and clinical course of IBC in the UK. Materials and methods: Patients with IBC diagnosed between 1997–2014 at fourteen UK and Irish hospitals were identified from local breast unit databases. Patient characteristics, tumour pathology and stage, and details of surgical, systemic and radiotherapy treatment and follow-up data were collected from electronic patient records and medical notes. Result: This retrospective review identified 445 patients with IBC accounting for 0.4–1.8% of invasive breast cancer cases. Median follow-up was 4.2 years. 53.2% of tumours were grade 3, 56.2% were oestrogen receptor positive, 31.3% were HER2 positive and 25.1% were triple negative. 20.7% of patients had distant metastases at presentation. Despite trimodality treatment in 86.4%, 40.1% of stage III patients developed distant metastases. Five-year overall survival (OS) was 61.0% for stage III and 21.4% for stage IV patients. Conclusions: This is the largest series of UK IBC patients reported to date. It indicates a lower incidence than in American series, but confirms that IBC has a high risk of recurrence with poor survival despite contemporary multi-modality therapy. A national strategy is required to facilitate translational research into this aggressive disease. Highlights: Previous studies of inflammatory breast cancer (IBC) in the UK have been limited to small single centre series. We performed a multi-centre retrospective review of IBC cases from 14 UK and Irish hospitals. IBC cases accounted for 0.4–1.8% of invasive breast cancer cases at these centres. Although 86.4% stage III patients received chemotherapy, surgery and radiotherapy, 40.1% developed distant metastases. Five-year overall survival (OS) was 61.0% for patients with stage III disease at presentation.